2022
DOI: 10.3390/life12060901
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Long COVID in the General Population: Sociodemographic and Health Correlates in a Cross-National Sample

Abstract: We aimed to gain knowledge of possible sociodemographic predictors of long COVID and whether long COVID was associated with health outcomes almost two years after the pandemic outbreak. There were 1649 adults who participated in the study by completing a cross-sectional online survey disseminated openly in Norway, the UK, the USA, and Australia between November 2021 and January 2022. Participants were defined as having long COVID based on self-reports that they had been infected by COVID-19 and were experienci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 45 publications
1
15
2
Order By: Relevance
“…et al where a 51% prevalence of “post COVID syndrome” in self-reported university students who experienced mild to moderate infection (not hospitalized) was reported [ 25 ], as well as a self-reported prevalence of 60% among Spanish participants with a history of hospitalization [ 26 ]. On the other hand, a self-reported investigation of 310 individuals from several countries (Norway, United Kingdom, United States and Australia) showed a lower prevalence (28.7%) of long-COVID sequalae when compared to our results [ 27 ], nevertheless, in a systematic review a prevalence of 43% was estimated at a global level [ 28 ].…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…et al where a 51% prevalence of “post COVID syndrome” in self-reported university students who experienced mild to moderate infection (not hospitalized) was reported [ 25 ], as well as a self-reported prevalence of 60% among Spanish participants with a history of hospitalization [ 26 ]. On the other hand, a self-reported investigation of 310 individuals from several countries (Norway, United Kingdom, United States and Australia) showed a lower prevalence (28.7%) of long-COVID sequalae when compared to our results [ 27 ], nevertheless, in a systematic review a prevalence of 43% was estimated at a global level [ 28 ].…”
Section: Discussioncontrasting
confidence: 88%
“…Regarding sex, it was evidenced that women presented more Long-COVID symptoms (feeling of anxiety, brittle hair, difficulty concentrating, headache, insomnia, nausea, neuritis, hair loss, memory defects, muscle loss, dry skin, easy crying, and brittle nails) when compared to men, findings similar to those presented by Sudre et al and Whitaker et al in self-report studies in the population of the United Kingdom [ 33 , 34 ], Mexico [ 35 ] and Spain [ 26 ]. While these differences may be because women are more likely to participate in this type of investigations and are more aware of their health, only one study has shown that men are more likely to develop long-COVID than women [ 27 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding sex, it was evidenced that women presented more post-acute symptoms (feeling of anxiety, brittle hair, difficulty concentrating, headache, insomnia, nausea, neuritis, hair loss, memory defects, muscle loss, dry skin, easy crying, and brittle nails) when compared to men, findings similar to those presented by Sudre et al and Whitaker et al in self-report studies in the population of the United Kingdom [32,33], Mexico [34] and Spain [25]. While these differences may be because women are more likely to participate in this type of investigations and are more aware of their health, only one study has shown that men are more likely to develop long-covid than women [26,35].…”
Section: Discussionsupporting
confidence: 75%
“…et al where a 51% prevalence of "post COVID syndrome" in self-reported university students who experienced mild to moderate infection (not hospitalized) was reported [24], as well as a self-reported prevalence of 60% among Spanish participants with a history of hospitalization [25]. On the other hand, a self-reported investigation of 310 individuals from several countries (Norway, United Kingdom, United States and Australia) showed a lower prevalence (28.7%) of long-COVID sequalae when compared to our results [26], nevertheless, in a systematic review a prevalence of 43% was estimated at a global level [27].…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation